3 - Whither African Development? A Preparatory for an African Alternative Reformulation of the Concept of Development - Wai, Zubairu (Africa Development, 2007)
Intended as a preparatory for an African alternative reformulation of the con- cept of development, this paper problematises Africa’s development experi- ence in order to understand the impasse that has characterised it. Three major concerns are addressed: first, development is historically examined as a politi- cally violent and oppressive, culturally deterministic and economically exploita- tive paradigm operating on a flawed logic. Second, it discusses the reconceptualisation of development as a global project in the current era of neo- liberal globalisation, and considers why problems of African development can- not be solved within the context of this equally flawed and problematic refor- mulation. Finally, the paper proposes ways in which development, rather than abandoned, might be reclaimed so as to allow for reformulations of indigenous African alternatives; that is, reformulated and anchored in indigenous concep- tions of social provisioning and the individual’s position within a community.